CONCEPTUAL PRINCIPLES OF LEGAL AND SCIENTIFIC ENSURING THE DEVELOPMENT OF THE AVIATION INDUSTRY OF UKRAINE - Panova, Oksana; Bilenchuk, Petro; Malii, Mykola (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2023)
Purpose: the conceptual principles of legal and scientific support for the development of the aerospace industry of Ukraine in the Electronic Age are considered. Methods: formal-logical, systemic-structural, comparative, historical, dogmatic methods were used in researching and forming the conceptual foundations of legal and scientific support for the development of the aerospace industry of Ukraine, and based on the methods of asymmetric analysis and synthesis, the future goals of this innovative industry were determined. Results: the task of further legal and scientific support for the development of the aerospace industry of Ukraine was updated, the need for intensive involvement and use of innovative technologies in the near future was noted, the need for further improvement of international space law and space law of Ukraine was emphasized. Discussion: the results of a comprehensive analytical approach regarding the further development of legal and scientific support for the aerospace industry of Ukraine, the need for timely and qualitative improvement of the norms of international and national space law of Ukraine, the formation of worldview creative views, ideas regarding the conceptual foundations of legal and scientific support for the development of the aerospace industry of Ukraine in the Electronic Age. It is impossible to overestimate the role of the space industry in today. Let’s list just a few examples: firstly, the creation of a complex of target equipment for observing the geophysical parameters of the ionosphere, the upper layers of the atmosphere and near-Earth space, the development of instruments for measuring the ozone layer, greenhouse gases and small components of the atmosphere; secondly, information and technical support and development of a system for continuous collection and processing of satellite monitoring data in the interests of the agricultural land monitoring system; thirdly, the development of methods for monitoring and forecasting wildfires and their consequences using geoinformation technologies; fourthly, improvement of technologies of the sectoral fisheries monitoring system; fifthly, the development of a system for remote monitoring of forest fires and foci of mass reproduction of harmful insects and forest diseases.